Building and applying a standard educational unit in school theater (an extracted research) (Journal of the College of Basic Education, 2023)
The general development of life usually results in the need for a lot of science in preparing a generation capable of assimilating the new tasks of life. As Iraq witnessed development in all areas of life, the field of education witnessed a great and clear development in its educational institutions, as education is no longer confined within the walls of schools and was not confined to On the forms of classroom education, but rather expanded, and the learner has a prominent role in the educational process. And it became necessary for him to rely on himself in acquiring information and skills that would help him in his practical life.Traditional teaching methods achieve the relative stability that they have come to receive from educational institutions and the educational community. However, the continuous change that occurs in the educational environment and what is related to it and affects it, such as the increase in the demand for learning and cognitive development, etc., requires educators to reconsider the teaching methods despite Which achieved relative stability and stability in order to determine the effectiveness of these methods in light of these variables. (Al-Tobji, 1983, p. 35)“The large number of student communities and the diversity of their academic levels, skills and culture, and their heterogeneity lead to varying individual differences between them and to the creation of educational problems, whether in the interaction between the students themselves or in the interaction between them and their teachers” (Al-Sheikhly, 1975, p. 29)And because the process of social interaction within educational institutions between students and their teachers during the educational process is closely related to several factors, including the size of the classroom, the number of students in the classroom, the ratio of their number to one teacher, and the followed teaching style, this density has produced some effects, including: